Legal Advocacy For Catfish Cultivation Groups As An Effort To Improve The Economy In Facing The Covid 19 Pandemic In Mojorang Agung Wondayu Village, Sidoarjo, East Java, Indonesia - Sutrisno; Mas Anienda Tien F; Rohmatul Faizah; Hervina Puspitosari (International Journal Of Community Service, 2021)
Empowerment of catfish advertising cultivation for the community can increase the income source of rural communities and also as an effort to expand employment opportunities for rural communities through the provision of existing land and water in the village of Mojorangagung Wondayu Sidoarjo, East Java, Indonesia. Fish farming business groups in running their business require a business license as a form of legality. Assistance and roles and cooperation with various related agencies are needed in the progress of fish farming business groups, for example,Cooperation with the Department of Agriculture and Food, Cooperation with Universities, one of which is with the National Development University "Veteran" East Java so that assistance can be carried out in managing its legality and can be carried out assistance in cultivation and marketing as well as various other collaborations with related agencies are also needed. The management of legal entities for fish farming groups is very important, apart from being an obligation some rights can be obtained by fish farming groups that have legal entities including being able to receive assistance from the government in the hope that fish farming business actors in the future can be independent and carry out sustainable fisheries business.